2017
DOI: 10.1093/mnras/stx3051
|View full text |Cite
|
Sign up to set email alerts
|

The 6-GHz Multibeam Maser Survey – III. Comparison between the MMB and HOPS

Abstract: We have compared the occurrence of 6.7-GHz and 12.2-GHz methanol masers with 22-GHz water masers and 6035-MHz excited-state OH masers in the 100 square degree region of the southern Galactic plane common to the Methanol Multibeam (MMB) and H 2 O southern Galactic Plane surveys (HOPS). We find the most populous star formation species to be 6.7-GHz methanol, followed by water, then 12.2-GHz and, finally, excited-state OH masers. We present association statistics, flux density (and luminosity where appropriate) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 60 publications
(132 reference statements)
3
19
2
Order By: Relevance
“…An ex-OH maser is taken to be associated with a 6.7 GHz source if the on-sky separation is less than 2.0 . Breen et al (2018) also identified associations between the 6.7 GHz MMB masers and the water masers from the HOPS data, with positional association a more complex task due to the less localised nature of water maser emission. The authors take this into account, and 6.7 GHz methanol maser is associated with a water maser if a HOPS maser spot falls within 2.0 arcsec.…”
Section: Identification Of Counterpart Masersmentioning
confidence: 80%
See 4 more Smart Citations
“…An ex-OH maser is taken to be associated with a 6.7 GHz source if the on-sky separation is less than 2.0 . Breen et al (2018) also identified associations between the 6.7 GHz MMB masers and the water masers from the HOPS data, with positional association a more complex task due to the less localised nature of water maser emission. The authors take this into account, and 6.7 GHz methanol maser is associated with a water maser if a HOPS maser spot falls within 2.0 arcsec.…”
Section: Identification Of Counterpart Masersmentioning
confidence: 80%
“…These were used to group detected masers into sites, 435 of which are associated with star formation. For this work, we use the association of these masers with MMB masers given in Breen et al (2018).…”
Section: Additional Maser Studiesmentioning
confidence: 99%
See 3 more Smart Citations